Real-world trends in incidence of bacterial sexually transmissible infections among gay and bisexual men using HIV pre-exposure prophylaxis (PrEP) in Australia following nationwide PrEP implementation: an analysis of sentinel surveillance data. Issue 8 (August 2022) - Traeger, Michael W; Guy, Rebecca; Asselin, Jason; Patel, Prital; Carter, Allison; Wright, Edwina J; Grulich, Andrew; McManus, Hamish; Fairley, Christopher K; Chow, Eric P F; McNulty, Anna; Finlayson, Robert; et al.
Summary: Background: Although data from large implementation trials suggest that sexually transmissible infection (STI) risk increases among gay and bisexual men who initiate HIV pre-exposure prophylaxis (PrEP), there are few data on the trends in population-level STI incidence in the years following widespread PrEP implementation. We aimed to describe trends in bacterial STI incidence among gay and bisexual men using PrEP across Australia in the context of broad PrEP availability through Australia's subsidised medicines scheme. Methods: We analysed linked clinical data from HIV-negative gay and bisexual men aged 16 years or older who had been prescribed PrEP across a sentinel surveillance clinical network, including 37 clinics in Australia, between Jan 1, 2016, and Dec 31, 2019. Patients were included if they had STI testing at least twice during the observation period. Repeat testing methods were used to calculate chlamydia, gonorrhoea, syphilis, and any STI incidence rates during individuals' periods of PrEP use. Incidence rate ratios (IRRs) for estimated change in incidence per half calendar year (6-month) period were calculated using negative binomial regression. Secondary analyses compared STI incidence rates across individuals initiating PrEP in each year from 2016 to 2019, as well as by length of time using PrEP (per each additional 6 months of PrEP use). Findings: 22 730 men were included in the analyses. During the observation period, 11 351 chlamydia infections were diagnosed in 6630 (30·1%) of 22 034 men over 25 991·2 person-years of PrEP use (incidence rate 43·7 cases [95% CI 42·9–44·5] per 100 person-years). Chlamydia incidence decreased from 48·7 cases per 100 person-years in July–December, 2016, to 42·0 cases per 100 person-years in July–December, 2019 (IRR for estimated change per 6-month period 0·98 [95% CI 0·97–0·99]; p=0·0031). 9391 gonorrhoea infections were diagnosed in 5885 (26·9%) of 21 845 men over 24 858·7 person-years of PrEP use (incidence rate 37·8 cases [95% CI 37·0–38·5] per 100 person-years). Gonorrhoea incidence decreased from 45·5 cases per 100 person-years in July–December, 2016, to 37·2 cases per 100 person-years in July–December, 2019 (IRR 0·97 [95% CI 0·96–0·98]; p<0·0001). Declines in chlamydia and gonorrhoea incidence were most prominent in the first 18 months of observation and incidence was stable thereafter. 2062 syphilis infections were diagnosed in 1488 (7·7%) of 19 262 men over 21 978·9 person-years of PrEP use (incidence rate 9·4 cases [95% CI 9·0–9·8] per 100 person-years). Syphilis incidence increased from 6·2 cases per 100 person-years in July–December, 2016, to 9·8 cases per 100 person-years in July–December, 2019 (IRR 1·08 [95% CI 1·05–1·10]; p<0·0001). Interpretation: Chlamydia and gonorrhoea incidence among gay and bisexual men using PrEP were highest in the early months of PrEP implementation in Australia and stabilised at slightly lower rates thereafter following wider PrEP uptake. Lower prospective STI risk among people initiating PrEP in later years contributed to the observed trends in STI incidence. Widespread PrEP implementation can contribute to increased STI screening and detection. Funding: Australian Department of Health, National Health and Medical Research Council.